Woman, native, other: Writing Postcoloniality and feminism - Minh-ha, Trinh T. (Indiana University Press, 1989)
Woman, Native, Other is located at the junction of a number of different fields and disciplines, and it genuinely succeeds in publishing the boundaries of these disciplines further ... In this first full-length study, Trinh Minh-ha examines post-colonial processes of displacement -- cultural hybridization and decentered realities, fragmented selves and multiple identities, marginal voices and languages of rupture. Working at the intersection of several fields -- women's studies, anthropology, critical cultural studies, literary criticism, and feminist theory, she juxtaposes numerous prevailing contemporary discourses in a form that questions the (male-is-norm) literary and theoretical establishment
Keywords: approches et analyses; arts; discipline; postcolonialisme; système colonial; systèmes d'oppressions; études littéraires